Outcome Evaluation of Active Surveillance in Low Risk Group Prostate Cancers - Shah Nawaz Areejo, Abdullah, Amer Abbas, Shahzad-Ur-Rehman, Zakir Khan, Muhammad Asif, (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To assess the outcomes of active surveillance evaluation in low risk prostate cancer patients. Study Design: Cohort study Place and Duration of Study: Department of Urology, Ghulam Muhammad Mahar Medical College Hospital (GMMMC), Sukkur from 1st August 2019 to 30th September 2022. Methodology: One hundred and ten patients suffering from prostate cancer with Gleason score upto 6 (low risk group prostate cancer) patients were enrolled. Active surveillance was done with 3 monthly check-up with physical examination and serum prostate specific antigen. Results: The mean age of the patients was 61.5±3.5 years. The Gleason score showed that majority of the cases were within the score of 6 (3+3) with highest having a clinical staging as T1c followed by T2b. The active surveillance outcomes showed on a median follow-up of 3 years that the upgrade on repetitive biopsies or prostatectomy was taken in 19 cases only with a proper treatment received in only 22 cases. Conclusion: Patients with active surveillance have increased rate of definitive treatment post initial diagnosis. Safety net hospital provides critical care and takes up active surveillance as a challenge. Keywords: Evaluation, Prostate, Molecular, Morbidity, Management